2023
DOI: 10.1093/g3journal/jkad068
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding misleading estimates using mtDNA heteroplasmy statistics to study bottleneck size and selection

Abstract: Mitochondrial DNA (mtDNA) heteroplasmy samples can shed light on vital developmental and genetic processes shaping mtDNA populations. The sample mean and sample variance of a set of heteroplasmy observations are typically used both to estimate bottleneck sizes and to perform fits to the theoretical “Kimura” distribution in seeking evidence for mtDNA selection. However, each of these applications raises problems. Sample statistics do not generally provide optimal fits to the Kimura distribution and so can give … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To this end, prior work generally consists of either theoretical modeling or empirical study of mitochondrial mutations, 29,43,[53][54][55] making it difficult to integrate theory with experiment. Although some modeling studies incorporate empirical data, 29,[55][56][57] these focus on heteroplasmy dynamics within organisms, or within parent-progeny lineages, making it difficult to combine the levels of selection into a complete evolutionary picture. To address these challenges, we developed a hybrid approach that integrates theoretical modeling with experiments designed to individually probe the levels of selection and the mutant frequency distribution.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, prior work generally consists of either theoretical modeling or empirical study of mitochondrial mutations, 29,43,[53][54][55] making it difficult to integrate theory with experiment. Although some modeling studies incorporate empirical data, 29,[55][56][57] these focus on heteroplasmy dynamics within organisms, or within parent-progeny lineages, making it difficult to combine the levels of selection into a complete evolutionary picture. To address these challenges, we developed a hybrid approach that integrates theoretical modeling with experiments designed to individually probe the levels of selection and the mutant frequency distribution.…”
Section: Discussionmentioning
confidence: 99%
“…We then asked whether the heteroplasmy shifts that we observed in LHON-edited or SILENT-edited cells can be explained by a simple model of drift based on the ‘Kimura’ distribution 36 , 37 . We found that the maximum likelihood fit of the Kimura distribution to our observed silent heteroplasmy distribution was very good (Extended Data Fig.…”
Section: Joint Distribution Of Silent and Missense Heteroplasmymentioning
confidence: 99%
“…For numerical convenience, we used a population size of N e = 50 in the numerical simulations. Following the usual parameterisation of the Kimura distribution for mtDNA work (Wonnapinij et al, 2008;Giannakis et al, 2023)…”
Section: Inference Of Segregation Dynamicsmentioning
confidence: 99%
“…1a). Importantly, our model considers individual heteroplasmy measurements (rather than fitting using coarse-grained, uncertain summary statistics like heteroplasmy variance), increasing the statistical power of our approach (Giannakis et al, 2023).…”
Section: Heteroplasmymentioning
confidence: 99%
See 1 more Smart Citation